Discussion on a thermobaric adsorption test method and its data processing for coal - Qinghua Ma; Xiaoyan Ji; Dong Li; Xuemei Zhang; Yaling Wei; Rong Chen (South African Journal of Chemical Engineering, 2024)
The measured thermobaric adsorption of anthracite coal “Vmeas” contains 12 pairs of testing results at different temperatures (18∼72 °C) and corresponding pressures (1∼19 MPa), simulating the buried depth of 100∼1900 meter has been published by Zhang Qingling in 2008. A temperature-pressure-adsorption equation (TPAE) has been used to regress the measured data, then to calculate the 12 pairs of thermobaric adsorption data “Vcal”. The relative error and the standard deviation between the Vmeas and the Vcal are calculated and used to verify TPAE's applicability for thermobaric adsorption data. The 3-dimensional TPAE surface is also used for verification. The other 3 sets of optimized thermobaric adsorptions (10 pairs, 8 pairs, and 6 pairs) have been created. To cover a range of temperature (18∼72 °C) and pressure (1∼19 MPa), there must be at least the minimum 6 pairs of thermobaric adsorptions including the lowest temperature 18 °C and pressure 1 MPa, and the highest temperature 72 °C and pressure 19 MPa.